Barriers and motivators for physical activity in community dwelling adults: a comprehensive systematic review protocol. (March 2015) - Alexander, Lyndsay; Cooper, Kay
Abstract : Review question/objective : The quantitative objective is to identify the barriers and motivators for the participation of community dwelling adults in physical activity. The qualitative objective is to identify the perceptions and experiences of community dwelling adults on the barriers and motivators to physical activity. The textual objective is to identify the issues related to barriers and motivators for the participation of community dwelling adults in physical activity. Background : The individual, health, economic and societal benefits of a physically active lifestyle are widely acknowledged. Benefits of a physically active lifestyle include an increase in physical, social and mental health and wellbeing, and a significantly reduced risk of developing non‐communicable conditions including cardiovascular disease, diabetes and obesity. However, despite these benefits, not all individuals meet the current UK or international guidelines for physical activity (PA).1, 2 Although Scottish PA levels have been reported as greater than other home countries, 3 the Scottish Health Survey has reported that only 62% of adults have met the UK PA guidelines.4 The reported values for home countries are thought to be an over‐estimation due to the acknowledged limitations of self‐report survey design.3 A recent review of the Scottish Physical Activity Strategy "Let's Make Scotland More Active" has concluded that there has been insufficient action at local levels in Scotland to impact on population PA levels.5, 6 The authors of this review have identified a need for commitment, resources and robust evaluation at local levels to address continued PA inequities. The Scottish Government has identified a number of targets for population participation in physical activity by 2022 and therefore it is important to understand what encourages people to participate in physical activity and what prevents participation at a more local level.7 In order to address this need, it is important to identify any barriers or motivators to PA in a community setting so that local agencies can target and plan appropriate interventions and services. Some barriers to physical activity have been identified to be related to safety, culture and access, 3 with the majority of published systematic reviews focused on environmental effects, 8, 9 or effects within ethnic minorities or disabilities.10, 11, 12 A search of the literature has failed to identify any comprehensive systematic reviews that identified barriers and motivators to physical activity in the community other than a systematic review protocol registered within PROSPERO for barriers and facilitators in physical activity among Muslim adolescents.13 This review will therefore systematically evaluate all evidence around barriers and motivators to physical activity in community dwelling adults. The results of this systematic review will be used to inform the planning and development of community interventions in the Scottish context, as well as identifying areas for future research.